Decomposing Central and Eastern Europe's trade: Extending the evidence - Robin Grözinger (Leibniz-Institut für Ost- und Südosteuropaforschung (IOS), 2020)
In the early nineties Central and East European Countries (CEEC) took considerable liberalisation efforts which led to visible changes in CEEC trade. In the period under observation, from 1995 to 2016, these countries recorded high growth rates, which exceeded the performance of other regions, such as the OECD and Russia. These trade developments are described and interpreted in this note on a descriptive rather than an analytical basis. First, trade volumes by goods categories are examined to account for what kind of goods are the major trade growth drivers. The expansion of CEEC imports and exports can be accounted for by trade growth specifically of goods used in production, i.e., parts and components, capital goods and transport equipment. It can be associated with the development of vertical production networks among the old EU member states and the new EU-8 countries. Examining EU-8 exports to and imports from Germany confirms this finding: EU-8 states tend to import parts and components and intermediate goods from Germany to produce and export parts and components or final capital goods to Germany. Using the notion of comparative advantage further helps to attribute the extensive development of vertical linkages with the CEEC to the similarity of sectoral productivity vectors between the CEEC and the rest of the world. Second, the effects of liberalisation on the variety versus the intensity of trade are described. The liberalisation of the CEEC economies is expressed by the strong rise in newly traded goods, especially goods used in production, rather than volume growth in already traded goods. Considering imports, a higher input variety might thereby signal a change of the economy's state of technology.
urn:nbn:de:101:1-2020122807095904272907
Keywords: F1; 330; CEEC; intensive margin; extensive margin; vertical production networks; comparative advantage